Without evaluation there is no innovation. Assessment of the instructional design of virtual postgraduate courses at the Universidad Autónoma de Occidente - Virginia López Nevárez; Francisco Javier Velázquez Sagahón (Apertura)
This study explores innovation as the generation of value by assessing the quality of instructional design in two virtual postgraduate programs at the Universidad Autónoma de Occidente (UAdeO). An instructional design evaluation tool tailored for online platforms was validated, focusing on the integration of innovative elements within these courses. A proof-of-concept (PoC) methodology was applied using an instrument that encompassed key dimensions of quality instructional design: Guidance, Content, Materials, Tasks, Tutoring, and Functionality. Twenty-nine external experts from universities outside UAdeO participated by accessing the virtual platform and evaluating the courses. The findings revealed a quality index of 80% for both programs, highlighting a need for improvement in the virtual tutoring dimension. The study emphasizes the potential of incorporating innovative approaches, such as artificial intelligence and adaptive learning tools, in tutorial support. The instrument’s validity was confirmed through Principal Component Analysis (PCA) using the R statistical software. This validated tool offers a robust framework for future research and comparative studies, enabling comprehensive and replicable instructional design evaluations.